Indicadores de desempenho como instrumento de gestão de lodo de estações de tratamento de esgoto - Gandolphi, Caroline (2023)
The improvement and efficiency of sanitary sewage systems depend on management from an integrated perspective. An important stage that composes the sewage systems is the management of the solid waste generated, however, in Brazil this issue is often neglected, characterized by incomplete treatment steps and doubt about the environmentally appropriate disposal of the sludge. This factor highlights the demand for the application of management tools to improve this sector, especially with regard to the sludge. A relevant document to assist in the coordination of management actions is the Standard ABNT NBR ISO 24511/2012, which advocates the use of Performance Indicators as an essential tool for managing sewage services. In this context, this research aims to analyze performance indicators related to the management of sanitary sewage services, collected from national and international organizations, and to identify, compile and analyze a set of indicators applicable to sludge management. Likewise, an evaluation of the application of this set of indicators was carried out to help manage the sludge generated in Wastewater Treatment Plants (WWTP), considering the precepts of NBR ISO 24511/2012 regarding the accuracy and reliability of the data. The analysis of the indicators reveals, among international sources, the majority of operational indicators, while among the national sources, the prevalence is of financial and economic indicators. For sewage sludge, 28 indicators were identified, only among international sources, which correspond to 5.5% of the total, they were compiled and complemented, resulting in 36 indicators for application in the analyzed WWTP. From the application of the set of indicators, the availability of data for each ETE and the degree of confidence of the variables and performance indicators were verified. Based on these results, and considering the difficulty in obtaining reliable data for applying the total of compiled indicators, a set of strategic performance indicators was proposed, applicable from a reduced number of variables and addressing the main aspects related to the sludge management, to be used for the management of this residue. Despite the incipience with the management of sewage sludge that occurs in Brazil confirmed by the results, the use of this set, associated with the method of evaluating the degree of confidence of the data, proves to be adequate as a management instrument for sewage sludge.